Thoái hóa đất và quá trình hoang mạc hóa ở vùng Nam Trung Bộ - Kỳ, Nguyễn Đình; Dân, Nguyễn Lập; Hà, Nguyễn Mạnh (Vietnam Journal of Earth Sciences, 2012)
SUMMARYThe soil degaradation and desertification in South Central VietnamThe soil degaradation and desertification are affects resulting from the loss of the ecological balance by the natural processes and socio-economical activities in the arid, semi-arid and dry sub-humidareas. According the geo-synthetization, the soil degradation is a main cause leading to the desertification.In Central Southern of Vietnam, the condition of the soil originating (from Da Nang to Binh Thuan area) is belonged to the monsoon of the tropical climate with 6-9 dry months. Particularly, the NinhThuan - Binh Thuan area has 8-9 dry months that is identical to a semi-arid area, occupying ~45,000 km2. The structure of the soil layer is complicated with 10 groups, 20 types of the soil layer, morethan 65,000 ha of the mountain land, and 265,000 ha of the sand-dune and sand beach.The area has high potential of soil degradation and it is happening strongly after seasons. One of the main reason of the soil erosion is water current in the steep area, by winds in the coastal sandy area, laterization in the hill area, and salinization in the coastal area, etc... In this area, the average soil loss by the water current is ranging from 400-800 ton/ha per year, in the places this number is up to1,000 ton/ha per year. Consequently, 48 % of the area in the upper-land has thin soil layer below 30 cm and over 30 % of the area in the lowland has light mechanical components. Furthermore, it is leading to the low water - bearing capacity of the soil, as well as increasing of the evaporation rate, promoting desertification processes in these areas.According to the world’s classification, 4 types of desertification are presented in the Central Southern of Vietnam as followed :- Sandy desert : this type is occupy about of 260,000 ha, mainly locating in Binh Thuan, Ninh Thuan and Binh Dinh provinces ;- Rocky-stone desert : this type of desert has about of 100,000 ha, distributing in Quang Ngai, Binh Dinh, Khanh Hoa, Ninh Thuan and Binh Thuan provinces ;- Dust desert : the total area of this type of desert has about 290,000 ha, comprising infertile gray soil and erode soil with grave and stone. They are distributed along the foot of the Truong Son Mountain to the plain land near the coastal line, from Quang Ngaito Binh Thuan provinces;- Salt desert: It has about of 49,000 ha and concentrated in Ninh Thuan and Binh Thuan pro-vinces. The rule of the distribution of the desertification is increase from the North to the South and from the East to the West in the South Central Vietnam, so that, creating the two desert bands, one is near the coast and other is at the foot of the Truong Son mountain. The trend of the soil degradation and desertification is increasing and spreading out, requiring more attention in controlling, managing, as well as recovering.